Exploring the relationship between fat mass index and metabolic syndrome among cancer patients in the U.S: An NHANES analysis - Xiuxiu Qiu; Qi Gao (Scientific Reports)
Abstract Data regarding the connection between Fat Mass Index (FMI) and Metabolic Syndrome (MetS) in cancer survivors remain limited. This study aimed to assess the association between FMI and the likelihood of MetS among cancer survivors by conducting a population-based cross-sectional study. This cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) to examine a sample of 799 adult cancer survivors, aged over 20 years old, spanning the years 1999–2006 and 2011–2018. MetS was defined according to the criteria established by the Adult Treatment Panel III of the National Cholesterol Education Program (NCEP). To explore the association between fat mass index FMI and the prevalence of MetS among cancer survivors, multivariate logistic regression analyses were conducted. Additionally, restricted cubic splines were used to assess both linear and nonlinear relationships between FMI and MetS. After adjusting for potential confounders, the logistic regression analysis of multistage weighted complex sampling data demonstrated that a higher FMI significantly increased the odds of developing MetS (odds ratio [OR] = 1.33, 95% confidence interval [CI]: 1.09–1.61, p = 0.01). This association remained robust when FMI was categorized into tertiles. Specifically, the adjusted ORs for MetS in the second and third tertiles were 4.80 (95% CI: 1.95–11.79) and 8.95 (95% CI: 2.51–31.94), respectively (p for trend = 0.001). Furthermore, our analysis indicated a significant nonlinear relationship between FMI and the likelihood of MetS (p < 0.0001). In this research, we discovered that an elevated FMI is significantly associated with a higher prevalence of MetS among cancer survivors in the U.S. adult population. These findings underscore the importance of managing body fat to prevent MetS in this group.